2001
DOI: 10.1051/0004-6361:20010524
|View full text |Cite
|
Sign up to set email alerts
|

A nanoflare heating model for the quiet solar corona

Abstract: Abstract. The energy input into the lower solar corona by flare evaporation events has been modeled according to the available observations for quiet regions. The question is addressed whether such heating events can provide the observed average level of the coronal emission measure and thus of the observed flux of extreme ultraviolet (EUV) and X-ray emission without contradicting the observed average power spectrum of the emission measure, the typical emission measure variations observed for individual pixels… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…That this indeed might be the case is also suggested by observations of the line widths of stellar C IV transition-layer lines observed by Wood et al (1997). In addition Mitra-Kraev & Benz (2001) have shown that the observed extreme ultraviolet (EUV) and X-ray emission fluxes from the quiet solar corona can be successfully described by a nanoflare heating model.…”
Section: Can Wave Heating Explain the Chromospheric Activity?mentioning
confidence: 57%
“…That this indeed might be the case is also suggested by observations of the line widths of stellar C IV transition-layer lines observed by Wood et al (1997). In addition Mitra-Kraev & Benz (2001) have shown that the observed extreme ultraviolet (EUV) and X-ray emission fluxes from the quiet solar corona can be successfully described by a nanoflare heating model.…”
Section: Can Wave Heating Explain the Chromospheric Activity?mentioning
confidence: 57%
“…In coronal heating studies, the value d = 3 is often taken for granted (Aschwanden et al 2000b;Parnell & Jupp 2000;Krucker & Benz 1998;Mitra-Kraev & Benz 2001). The analysis conducted here justifies this choice speaking in favor of a 3D emitting plasma volume, as opposed to more complex geometries described by d < 3 as predicted by some statistical-physical models (see , and references therein).…”
Section: Scaling Of Emission Eventsmentioning
confidence: 78%
“…First of all, the majority of nanoflares (and therefore, individual AQN annihilation events) must be below the resolution of solar telescopes and they must interact sufficiently with the corona to deposit the majority of the available energy in the TR rather than at lower radii. According to [29] the resolution limit for flares is E res ≈ 3 × 10 24 erg ≈ 2 × 10 27 m p c 2 which implies that the majority of AQN must have a baryon number below B ∼ 10 27 or, alternatively, that only a small fraction of their mass is able to annihilate in the Corona, though the later possibility is disfavoured by the analysis of [6].…”
Section: Solar Corona Observationsmentioning
confidence: 99%
“…While the number of collisions (29) is comparable with the total baryon charge B of a nugget, the probability of annihilation is quiet small. Instead, the most likely interaction of any incident matter with the nugget is total reflection due to a number of reasons: the sharp boundary between hadronic and CS phases such that only a very small fraction κ(T ) 1 of collisions represented by (29) will result in an annihilation. We refer to Appendix C for order of magnitude estimates supporting the main claim that κ(T ) 1.…”
Section: Pre-bbn Evolutionmentioning
confidence: 99%